The Concept of Moderation as an Effort to Prevent Verbal Violence and Bullying Behavior - Dini Arifah Nihayati; Ela Munifatus Sakdiyah (AL-THIFL : Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Between January 2025 and October 2025, several cases of verbal violence and bullying emerged, including a bullying case in Cigugur District, West Java, involving a junior high school student. A bullying case that resulted in death in Riau, and the destruction of a Christian prayer house in Padang. The rejection of a church construction in Depok, and a case of bullying and intolerance at SDN Jomin Barat II. Meanwhile, acts of verbal violence and bullying damage social relations in society. Verbal violence and bullying are forms of social deviation and intolerance. Moderation, as a maintainer of unity, offers tolerance and respect for differences. Therefore, the author wants to examine efforts to prevent verbal violence and bullying behavior according to the concept of moderation. This research is a library research. Moderation theory was chosen as a tool because moderation analysis offers solutions to foster a culture of peace and respect for others. The author obtained data from books and other scientific works, both printed and written. The results of the study indicate that the application of moderation values plays an important role in character formation and a social environment that is empathetic, inclusive, and free from violence